Long‐Term Interactions between the Roman City of Ostia and Its Paleomeander, Tiber Delta, Italy. Issue 2 (16th October 2016) - Salomon, Ferréol; Goiran, Jean‐Philippe; Pannuzi, Simona; Djerbi, Hatem; Rosa, Carlo
Abstract : This study examines the long‐term interactions between the well‐known Roman city of Ostia and a river meander. Located at the mouth of the Tiber river, Ostia was a major harbor city that connected Rome to the Mediterranean Sea. Based on aerial photography and borehole analysis, the paleodynamics of the Fiume Morto's paleomeander are understood to be linked to the urban evolution of the city of Ostia. Four periods of evolution have been identified as a result of this interdisciplinary work: (1) the foundation of Ostia's urban center, in the 4th to 3rd century BC, occurred when the meander already existed; (2) between the 4th century BC and the 3rd century AD, human/environmental interactions contributed to the compound growth of the meander that possibly eroded an important Roman road linking Ostia to Rome; (3) from the Imperial period until the meander was cut off in AD 1557–1562, the constricted meander channel at the apex led to the stability of the downstream river channel; (4) the cutoff of the paleomeander was completed in 1562, leading to the filling of the paleochannel. These successive phases of channel evolution mark changing fluvial risks from the Roman period to today.